Fungsi Pengaturan Sistem Pendidikan Pesantren Sebagai Instrumen Terwujudnya Manusia Yang Unggul - Aristo Lanang Langgeng Asmoro; Lego Karjoko; Sapto Hermawan (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
The regulation of the pesantren education system provides a legal guarantee for the continuity of pesantren education in Indonesia. The regulation is expected to be an instrument in realizing superior human beings. Research on the regulatory function of pesantren aims to find out more about the regulation of pesantren. The regulation is dissected to find how the pesantren regulation regulates the entire education system that takes place in the pesantren and then looks for the relationship between the correct regulation and the realization of superior human beings. Using a juridical-normative research approach, this research tries to comprehensively analyze Law No. 18/2019 on Pesantren. Law No. 18/2019 on Pesantren has regulated in detail how pesantren are organized. Equipped with the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 30 of 2020 concerning the Establishment and Implementation of Islamic Boarding Schools and the Regulation of the Minister of Religious Affairs of the Republic of Indonesia Number 31 of 2020 concerning Islamic Boarding School Education, the series of arrangements then work in harmony to oversee the running of Islamic boarding schools which then produce generations of superior humans.